2003
DOI: 10.1046/j.1467-789x.2003.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss causes increased mortality: cons

Abstract: Short-term studies indicate that intentional weight loss (IWL) among obese persons significantly improves health variables that are often precursors or markers of chronic diseases (e.g. heart diseases, type-2 diabetes). Hence, it is logical to assume that IWL among obese persons would lead to increased longevity. On the whole, epidemiological studies, including recent ones that use conservative analytic approaches such as distinguishing between apparently IWL and unintentional weight loss (UWL), adjusting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
74
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 36 publications
0
74
1
Order By: Relevance
“…Nutrition Research Reviews relative risk (RR) of all-cause mortality (13,14) . Methodological problems have also been identified, for example, the method by which the weight loss was achieved has usually not been reported (although dietary energy restriction is likely to have been a major factor), while weight changes before and after the recording periods have usually not been determined (12 -16) .…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition Research Reviews relative risk (RR) of all-cause mortality (13,14) . Methodological problems have also been identified, for example, the method by which the weight loss was achieved has usually not been reported (although dietary energy restriction is likely to have been a major factor), while weight changes before and after the recording periods have usually not been determined (12 -16) .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] However, the results are not consistent. 16,17 Variations in occurrence of pre-existing disease, sub-clinical disease, smoking, changes in body composition or fat distribution have been suggested to explain, in part, the elevated risk among those who lose weight. 10,11,18,19 Although studies have shown that even after careful confounder control and exclusion of subjects with preexisting disease, weight loss still seems an independent risk factor for premature death.…”
Section: Introductionmentioning
confidence: 99%
“…The primary limitation of the observational literature on weight change and mortality is the lack of information about weight loss intention (10,11). The weightlosing population includes an admixture of individuals losing weight on purpose and those who lose weight unintentionally.…”
mentioning
confidence: 99%